Everyone's table : global recipes for modern health - Gourdet, Gregory; Goode, J. J. (Harper Wave, an imprint of HarperCollinsPublishers, 2021)
"Beloved Top Chef star Gregory Gourdet's groundbreaking cookbook has the culinary sophistication and delight of Yottam Ottolenghi books and goes a step further, featuring only healthy recipes free of gluten, dairy, soy, refined sugar, and legumes"--